Pengelolaan Dana Lembaga Filantropi Islam Dalam Pengembangan Ekonomi Umat - Deden Gandana Madjakusumah; Udin Saripudin (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
Purpose: This paper aims to gather information about the management of ZISWAF through literature review. Methods: This study uses a qualitative approach to describe findings from facts and reality in society with a phenomenology approach. A literature review and documentation are conducted to collect the data. Finding: ZISWAF funds can be maximized for the economic development of the people, but currently these funds are still much engaged in the area of social service activities, charity assistance, compensation for orphans, Madrasah development, and others. Even tend to ignore the interests of other Muslims such as legal aid, child protection, public policy advocacy, women's empowerment, and several other important agendas, still lacking support from the utilization of philanthropic funds in addition to efforts to find out the potential of Islamic philanthropy and its impact on the economic development of the people, especially poor people or poor people.